Landscapes of pilgrimage in Medieval Britain - Locker, Martin (Archaeopress archaeology., 2015)
This work seeks to address the journeying context of pilgrimage within the landscapes of Medieval Britain. Using four case studies, an interdisciplinary methodology developed by the author is applied to four different geographical and cultural areas of Britain (Norfolk, Wiltshire/Hampshire, Flintshire/Denbighshire and Cornwall), to investigate the practicalities of travel along the Medieval road network including the routes themselves, accommodation, the built environments and natural topographies encountered.